2001
DOI: 10.1038/89297
|View full text |Cite
|
Sign up to set email alerts
|

A plant-based multicomponent vaccine protects mice from enteric diseases

Abstract: Cholera toxin (CT) B and A2 subunit complementary DNAs (cDNAs) were fused to a rotavirus enterotoxin and enterotoxigenic Escherichia coli fimbrial antigen genes and transferred into potato. Immunoblot and enzyme-linked immunosorbent assay (ELISA) results indicated that the fusion antigens were synthesized in transformed tuber tissues and assembled into cholera holotoxin-like structures that retained enterocyte-binding affinity. Orally immunized mice generated detectable levels of serum and intestinal antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(119 citation statements)
references
References 26 publications
3
115
1
Order By: Relevance
“…To allow the efficient presentation of the P1 peptide to the mucosaassociated lymphoid tissue, while maintaining the structural integrity of the P1 peptide, we created a translational fusion between the C terminus of CTB and the peptide. The epithelialbinding subunits of bacterial enterotoxins such as CTB (41,42) and the homologous B subunit of the heat labile toxin of E. coli (31,34,43) are known to be potent mucosal immunogens, which can efficiently present fused antigenic determinants to the immune system. Based on the ability of CTB-P1, but not CTB, to bind GalCer in vitro (data not shown), and the aggregation of CTB-P1 oligomers into larger oligomeric structures (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…To allow the efficient presentation of the P1 peptide to the mucosaassociated lymphoid tissue, while maintaining the structural integrity of the P1 peptide, we created a translational fusion between the C terminus of CTB and the peptide. The epithelialbinding subunits of bacterial enterotoxins such as CTB (41,42) and the homologous B subunit of the heat labile toxin of E. coli (31,34,43) are known to be potent mucosal immunogens, which can efficiently present fused antigenic determinants to the immune system. Based on the ability of CTB-P1, but not CTB, to bind GalCer in vitro (data not shown), and the aggregation of CTB-P1 oligomers into larger oligomeric structures (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As it is a potential mucosal and parenteral adjuvant and an effective carrier for chemically or genetically linked antigens, CT-B has often been expressed in the form of fusion proteins with antigens which do not induce sufficient immune response when orally applied on their own, much like LT-B. Examples of such use are CT-B-neutralizing epitope of the porcine epidemic diarrhea virus fusion protein (sCTB-sCOE) in lettuce (Huy et al, 2011), CT-Brabies glycoprotein fusion protein expressed in tobacco seeds (Tiwari et al, 2009), CT-B-Vibrio cholera accessory colonization factor subunit A (ACFA) fusion in tomato (Sharma et al, 2008), fusion of simian-human immunodeficiency virus regulatory sequence and CT-B , simian immunodeficiency virus Gag p27 capside protein-CT-B fusion (Kim et al, 2004a) and CT-B-anthrax lethal factor fusion in potato leaf , CT-B-human insulin B chain in tobacco (Li et al, 2006) and CT-B-rotavirus enterotoxin NSP4 fusion protein in potato tubers (Yu and Langridge, 2001). Expression levels of CT-B in most plant systems were 0.01 -1 % TSP, with the lowest yield of 0.04 % TSP in tomato leaf and fruit (Jani et al, 2002) and the highest yield of 4 % TSP in tobacco leaf (Daniell et al, 2001).…”
Section: Cholera Toxin Subunit Bmentioning
confidence: 99%
“…This confirmed that foreign proteins can be immunogenic when presented to the mucosal immune system via an orally delivered transgenic potato. A multicomponent plant-based vaccine comprised of cholera toxin complementary DNA fused to a rotavirus enterotoxin and enterotoxigenic E. coli fimbrae antigen genes was expressed in transgenic potatoes (Yu & Langrióge, 2001 Fig. 3.…”
Section: Support the Immune Systemmentioning
confidence: 99%